School organization and the mobilization of teachers and students in the use of a new general secondary education curriculum in East Timor - Ana Margarida Capelo; Isabel Cabrita (Springer, 2015)
Given that reforms involving how to deal with the past are extremely difficult, especially when the past involves memories of victimization, death, and destruction so widespread that a high percentage of the population is affected, the main purpose of this article is to describe how the general secondary education (GSE) curriculum in East Timor -an ancient Portuguese colony- is organized in terms of principles and objectives, themes, and methodological guidelines that give priority to assisting students to minimize or manage problems associated with conflict. Subsequently, the current state of GSE is characterized, in terms of school organization and logistics, and mobilization of teachers and students in using the new curriculum. The empirical results show that curricular materials incorporate aspects that can contribute to understanding and minimizing or managing problems created by the conflict, as well as contributing to avoid new conflicts. Nevertheless, although textbooks incorporate these aspects and teachers and students express interest in use them, problems remain regarding their appropriate usage due to numerous factors such as: logistics; school organization and poor teacher skills, despite training given and continued focused investment.